Proceedings of the 6th International Conference on Recrystallization and Grain Growth (ReX&GG 2016) - Holm, Elizabeth; Farjami, Susan; Manohar, Priyadarshan; Rohrer, Gregory; Rollett, Anthony; Srolovitz, David; Weiland, Hasso; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This collection represents a cross-section of the papers presented at the 6th International Conference on Recrystallization and Grain Growth. The volume is divided into nine sections: • Grain growth theory and simulation • Recrystallization theory and simulation • Low carbon and IF steels • High strength steels • Electrical steels • Stainless steels • Aluminum and magnesium alloys • Nickel and nickel based superalloys • Unconventional and advanced materials.
Keywords: Materials -- Analysis; Ceramic materials; Materials; Characterization and Analytical Technique; Ceramics; Materials Engineering